Monetary Policy and Innovation During Recession in Indonesia - jeffry sebayang; Ahmad Albar Tanjung; Sukardi Sukardi (Jurnal Ekonomi Pembangunan, 2022)
The COVID-19 pandemic affected global economic growth, including Indonesia's economic recession for four quarters from Q2 2020 to Q1 2021. This study uses Schumpeter's growth theory to analyze the interest rate policies and innovations that encourage economic growth in Indonesia in the long term. This study uses a quantitative approach with the Auto Regressive Distributed Lag (ARDL) model with the variables of GDP, BI interest rates, consumption, innovation, and investment credit. The study results show that Bank Indonesia's accommodative interest rate policy with low-interest rates during the recession due to the Covid-19 pandemic positively influences economic growth. However, in the long-term, interest rates must compete with interest rates from other countries to encourage investment capital flows to Indonesia. The findings show that innovation has not yet affected economic growth in Indonesia, but economic growth fosters innovation to accelerate technology transfer from developed countries through foreign investment. Therefore, the support of the Government and Bank of Indonesia to provide incentives through tax breaks and low-interest rates to business actors developing R&D and innovation will encourage accelerating technology and innovation growth in Indonesia.